Capsaicin: current understanding in therapeutic effects, drug interaction, and bioavailability - Chan, Suk Huei; Azlan, Azrina; Ismail, Amin; Shafie, Nurul Husna (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Capsaicin (N-vanillyl-8-methyl-6-(E)-none amide) is a unique and significant compound from group component of capsaicinoids. This component can only be found in the plants from the Capsicum genus. It is the primary source of pungency or spiciness of chilli pepper. Traditionally, capsaicin has been used to alleviate pain. Recently, some studies showed significant therapeutic effects of capsaicin in many diseases such as diabetes, hypertension, cancer and obesity. Determination of the most effective dosage used and underlying working mechanism of capsaicin are still in progress. Currently, capsaicin research, especially in drug interaction and encapsulation technologies, has not been reviewed. We aim to report current experimental evidence of capsaicin research focusing on its pharmacological properties, interaction with drugs and ways to improve the bioavailability of capsaicin. It is essential to provide a general orientation for further investigation that can discover more potency of capsaicin usage as a medicinal supplement to treat various diseases.